#### Answer

m$\angle$EFH = 67.5$^{\circ}$

#### Work Step by Step

We know that the measure of $\angle$EFG is 90$^{\circ}$ because we are given that it is right.
Using the Angle Addition Postulate, m$\angle$EFH+ m$\angle$HFG=m$\angle$EFG.
We are also given that m$\angle$EFH = 3*m$\angle$HFG and m$\angle$HFG=2$x$-6
Using the AAP, it can be concluded that 4*m$\angle$HFG = m$\angle$EFG
With substitution, 4*m$\angle$HFG = 90$^{\circ}$
Then, m$\angle$HFG =(90/4)$^{\circ}$, or 22.5$^{\circ}$
Using substitution once more, m$\angle$EFH=3*(22.5$^{\circ}$)
Finally, after multiplying by 3, m$\angle$EFH=67.5$^{\circ}$